An archaeology of counter-insurgency: exploring the materiality and memory of Cuban reconcentration camps (1895-1898) - Martí, Alberto P. (2017)
During the Cuban War of Independence (1895-1898), the Spanish military authorities put into practice a radical counter-insurgency strategy known as reconcentration. Usually identified as the context in which the modern concept of concentration camp emerged, that policy of mass relocation of the civilian population resulted in tens of thousands of victims, mainly due to starvation, poor sanitation, and the spread of epidemic diseases. This thesis analyses how that process was actually implemented on the ground, combining historical sources, oral tradition and the archaeological investigation of the physical effects that those measures had on the urban and rural landscapes. Through that approach, and using several case studies from the western province of Pinar del Río, this research offers new insights about the material and spatial transformations that took place during the conflict. It also establishes an innovative model for undertaking the study of later episodes in which regular armies had similarly resorted to reconcentration as a way to impose a complete segregation between guerrilla fighters and non-combatants.